Study Of Blood Pressure Lowering Effects Of Labisia Pumila (Blume) Merz Var. Alata Extracts And Its Mechanism Of Actions In Spontaneously Hypertensive Rats - Manshor, Nurul Maizan (2023)
Hypertension is major risk for cardiovascular complications such as stroke, myocardial infarction, ischemic heart disease and cardiac failure. Herbal medicines is an important element for possible alternative treatments or novel drug discovery for hypertension. Traditionally, Labisia pumila (Blume) Merz var. alata was used in maintaining women's health especially in the post-menstrual and post-partum’s conditions. In this study, vasorelaxant effects of Labisia pumila (Blume) Merz var. alata extracts on blood pressure of spontaneously hypertensive rats (SHR) were studied. Labisia pumila (Blume) Merz var. alata were extracted sequentially in solvents with different polarity. SHR were treated once orally daily for 28 days with Labisia pumila (Blume) Merz var. alata petroleum ether extract (LPPET), chloroform extract (LPCHLOR), methanol extract (LPMEOH) and water extract (LPWE) at the dose of 500 mg/kg/day. The systolic blood pressure (SBP) was non-invasively measured in conscious SHR by tailcuff method. The blood pressure lowering effects of Labisia pumila (Blume) Merz var. alata and its mechanisms were further carried out in anaesthetised-SHR, pithed-SHR and isolated aortic ring of SHR. Agonists and antagonists (L-NAME, indomethacin, methylene blue, ODQ, atropine, hexamethonium, prazosin and propranolol) were used for the mechanism studies.